2007
DOI: 10.1093/ndt/gfl636
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetic and pre-diabetic state on development of contrast-induced nephropathy in patients with chronic kidney disease

Abstract: Our data support that patients with DM are at a higher risk of developing CIN, but patients with pre-DM are not at as high a risk for developing CIN as diabetes patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 29 publications
5
67
1
5
Order By: Relevance
“…Therefore, the hyperglycemia itself makes the kidney more susceptible to CIAKI. 22 Several in vitro studies also 11,12 demonstrated that high-glucose condition enhanced the susceptibility of renal cells to the cytotoxic effects (apoptosis) of both the HOCM and LOCM. In other words, the combination of high-glucose and contrast media has a synergistic effect on accentuating renal tubular apoptosis and therefore increasing the risk of CIAKI.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the hyperglycemia itself makes the kidney more susceptible to CIAKI. 22 Several in vitro studies also 11,12 demonstrated that high-glucose condition enhanced the susceptibility of renal cells to the cytotoxic effects (apoptosis) of both the HOCM and LOCM. In other words, the combination of high-glucose and contrast media has a synergistic effect on accentuating renal tubular apoptosis and therefore increasing the risk of CIAKI.…”
Section: Discussionmentioning
confidence: 99%
“…7 Many studies have found Diabetes Mellitus (DM) as an independent risk factor for CIN. 5,15,30 Toprak et al showed that in patients with preexisting renal insufficiency, Diabetes Mellitus independently increased the risk of development of CIN and need for dialysis as opposed to pre-DM and Normal Fasting states, 31 while Berns showed that the incidence of CIN in diabetics was increased if serum creatinine is more than 4.0 mg% compared to 2 to 4 mg%. Clearly, there is a synergistic effect of diabetes and pre existing renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In study by Berns et al [1], CIN occurred in 27% of diabetics with baseline serum creatinine 2.0 to 4.0 mg/dL and in 81% of those with serum creatinine >4.0 mg/dL. In a study by Toprak et al [28], a total of 421 patients with CockcroftGauldt estimated creatinine clearance between 15 and 60 mL/min were divided into three groups: diabetes mellitus (n ¼ 137; glucose 126 mg/dL), pre-diabetes (n ¼ 140; glucose between 100 and 125 mg/dL), and normal fasting glucose (n ¼ 144; glucose < 100 mg/ dL). CIN, defined as an increase of 25% in creatinine over baseline within 48 hr of angiography, occurred in 20% of diabetics, 11.4% of pre-diabetics, and 5.5% of patients with normal fasting glucose level.…”
Section: Diabetes Mellitusmentioning
confidence: 94%